Effect of Installation Platform on Bearing Capacity of an Offshore Monopile Foundation - Fabo, Chen; Ben, He; Peng, Gao; Xiangming, Ge; Yong, Zhou; Weijiang, Chu (Frontiers in Physics, 2022)
An installation platform will disturb the natural seabed adjacent to a monopile and, consequently, affects the bearing capacity of the monopile foundation. Thus, consideration of the influence of installation disturbance is required in the monopile design, which can also save a fraction of the construction costs and avoid security risks. It was found in a sensitivity analysis, depending on the numerical simulations for an offshore monopile foundation installed using an installation platform, that the bearing capacities of the monopile were reduced by the penetration and extraction of the support legs of the installation platform, which were, a reduction of about 7% of the horizontal bearing capacity of the monopile (decreasing with a larger diameter of the monopile), about 2% of the ultimate bending moment, and almost no reduction of the vertical bearing capacity. For the monopile specifically subjected to the combined loads, it was found in SLS that horizontal displacement and rotation at the mudline increased by about 5.13% and 2.12%, respectively, and internal forces increased by about 3.29%–9.87%; and the horizontal displacement and the rotation at the mudline increased by about 4.56% and 2.79% in ULS, respectively, and the internal forces increased by about 3.49%–7.79% in the ULS. The study on the effects of the disturbance of the installation platform can be an important suggestion for the engineer in monopile design.